The Attenuating Effect of High-Intensity Interval Training and Nicotinamide Mononucleotide Supplementation on Aging-Related Oxidative Stress in Rat's Heart Tissue - Sakineh Taheri; Sajad Arshadi; Abdolali Banaeifar; Vahid Imanipour (Vesnu Publications, 2020)
Introduction: Numerous studies have shown attenuating effects of nicotinamide mononucleotide (NMN) and high-intensity interval exercise (HIIT) training on reducing oxidative stress. Therefore, in the present study, we evaluated the effect of HIIT and NMN supplementation on the oxidative stress markers in cardiac tissue of rats.Materials and Methods: 48 sprago dauli rats with an average age of 8 to 10 months were randomly divided into 6 groups of pretest control, control, sham (normal saline), HIIT, NMN supplementation, and combination (HIIT + NMN). The HIIT and combination groups performed HIIT on the treadmill for 8 weeks, 3 sessions per week. NMN with a dose of 500 mg per kilogram body weight was administered intra-peritoneally in the NMN and combination groups. 24 hours after the last training and NMN administration, the animals were sacrificed, and their hearts were removed for evaluating oxidative stress factors [malondialdehyde (MDA), protein carbonyl (PC), superoxide dismutase (SOD), and glutathione peroxidase (GPx)]. One-way ANOVA test was used for statistical analysis.Results: The expression of GPx gene in the groups receiving NMN, HIIT, and combination was significantly higher compared to the pretest control, control, and sham groups (P < 0.050). Moreover, the levels of MDA and PC were lower in NMN, HIIT, and combination groups compared to the pre-test control, control, and sham (P < 0.050). The highest reduction was seen in the combination group (P < 0.001).Conclusion: It seems that regular consumption of NMN and/or HIIT may attenuate oxidative stress in the cardiac tissue; however, combinations of NMN and HIIT significantly improves the effects of sole interventions.